Reliability enhancement and voltage profile improvement of distribution network using optimal capacity allocation and placement of distributed energy resources. (July 2021) - Agajie, Takele Ferede; Khan, Baseem; Guerrero, Josep M.; Mahela, Om prakash
Abstract: In the radial distribution system, reliability is the most critical performance criterion. Additionally, optimizing the voltage profile is critical. This work proposed the optimal placement of distributed energy resources (DERs) to enhance the reliability and improve the voltage profile of the distribution feeder. To perform this research, two practical feeders of the Debre Markos ( D / M ) city distribution network, Ethiopia were used, which were affected by the outages. A composite system adequacy assessment, which includes the two main components of the power grid, i.e. generation and distribution, is performed using Monte Carlo simulation. The computed results show that integrating DER units improved the overall system's reliability. Further, the effect of varying DER penetration on reliability and voltage profile is also analyzed. ETAP and DIgSILENT software environments are used to perform this research. Graphical abstract: Image, graphical abstract